2016
DOI: 10.17245/jdapm.2016.16.2.103
|View full text |Cite
|
Sign up to set email alerts
|

Identifying the more suitable nostril for nasotracheal intubation using radiographs

Abstract: BackgroundOne nostril must be selected for nasotracheal intubation. In some cases, structural anomalies within the nasal cavity hinder the insertion of the tube or complications, such as epistaxis, develop. This study examined the possibility of using radiography to select the nostril that would induce fewer complications.MethodsFour hundred and five patients who underwent nasotracheal intubation under general anesthesia were studied. A 7.0-mm internal diameter nasal right angle endotracheal (RAE) tube and 6.5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 17 publications
0
13
0
Order By: Relevance
“…There are many known ways to reduce epistaxis during nasotracheal intubation. Dipping a tracheal tube into a warm saline for thermosoftening [21][22][23], lubricating with xylocaine jelly [24], using a vasoconstrictor [25], using a tracheal tube with a smaller internal diameter than oral intubation [1], using radiographs to select more appropriate nostril [26], and if there is no difference between both nostrils, intubation with right nostrils is a typical way to reduce bleeding [27]. Tube passing underneath the inferior turbinate has also been recently suggested as a way to reduce epistaxis [28].…”
Section: Discussionmentioning
confidence: 99%
“…There are many known ways to reduce epistaxis during nasotracheal intubation. Dipping a tracheal tube into a warm saline for thermosoftening [21][22][23], lubricating with xylocaine jelly [24], using a vasoconstrictor [25], using a tracheal tube with a smaller internal diameter than oral intubation [1], using radiographs to select more appropriate nostril [26], and if there is no difference between both nostrils, intubation with right nostrils is a typical way to reduce bleeding [27]. Tube passing underneath the inferior turbinate has also been recently suggested as a way to reduce epistaxis [28].…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have claimed that the choice of the left nostril by orthognathic surgeons is more beneficial 28 . Chi et al 29 showed no significant relationship between the choice of the right or left nasal passage and incidence of complications in NTI. Some studies have suggested that the selection of the left nostril during NTI increases the complication rates 30 .…”
Section: Discussionmentioning
confidence: 99%
“…Flexible endoscopy also allows for detailed examination of the entire nasal cavity for nostril selection [2][3][4]. Depending on the patient's condition, methods such as facial radiography, CT, and MRI can be used to examine anatomical and pathological abnormalities such as SD [23,24].…”
Section: Considerations For Nasotracheal Intubation 1 Selection Of the Position Of The Nostril For Intubationmentioning
confidence: 99%